Gastric emptying in marathon runners. Issue 2 (February 1989) - Carrió, I; Estorch, M; Serra-Grima, R; Ginjaume, M; Notivol, R; Calabuig, R; Vilardell, F
Abstract : Radionuclide gastric emptying studies using 99m-Tc human serum albumin egg omelette have been carried out in 10 long distance runners at rest and during a 90 minute run at sustained speed. Resting values are compared with controls comprising 10 sedentary subjects. Runners show a significantly accelerated basal gastric emptying (runners t 1/2 = 67.7 (5.9) min; sedentaries t 1/2 = 85.3 (4.5) min, p less than 0.001). The exercise had no significant effect on gastric emptying in these trained subjects (exercise t 1/2 = 66.8 (5.9) min, p = NS), suggesting adaptation to exercise.